Genome-Wide Identification of PLATZ Transcription Factors in Ginkgo biloba L. and Their Expression Characteristics During Seed Development - Han, Xin; Rong, Hao; Tian, Yating; Qu, Yanshu; Xu, Meng; Xu, Li-an (Frontiers in Plant Science, 2022)
Plant AT-rich protein and zinc-binding protein (PLATZ) is a class of plant-specific zinc-dependent DNA-binding protein that binds to A/T-rich DNA sequences. PLATZ plays an important role in seed development, water tolerance, and cell proliferation in early plant growth. In this study, 11 GbPLATZs were identified from the ginkgo genome with complete PLATZ conserved domains, which represents a smaller number compared with angiosperms. Multi-species phylogenetic analysis showed that PLATZ genes were conserved in seed plants, and the 11 members were represented by four groups, among which group I and II were closely related. Analysis of gene structures, sequence module characteristics, and expression patterns showed that GbPLATZs were similar within and differed between groups. RNA-seq and qRT-PCR results showed that GbPLATZs had distinct expression patterns. Most genes were associated with seed development, among which six genes were highly related. Subcellular localization experiments showed that six GbPLATZ proteins related to seed development were localized in the nucleus, suggesting that they might function as traditional transcription factors. This study provides a basis for understanding the structural differentiation, evolutionary characteristics, expression profile, and potential functions of PLATZ transcription factors in Ginkgo biloba.